An Analysis of the Effect of Perceived Ease of Use, Perceived Usefulness, and Social Influence on the Impulsive Buying Behavior of Generation Z Users of the TikTok PayLater Feature in DKI Jakarta - Bintang Muhamad Harsya; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
This research seeks to examine how Perceived Ease of Use, Perceived Usefulness, and Social Influence affect impulsive buying behavior among Generation Z individuals in the DKI Jakarta region. The digital economy transformation in Indonesia has shifted from the traditional e-commerce model to a more integrated social commerce ecosystem, with TikTok Shop as one of the major players. The emergence of TikTok Paylater as a Buy Now Pay Later financial service innovation has created a phenomenon of shopping without financial barriers, which has significantly influenced the consumption behavior of Generation Z. This research uses the TAM theoretical framework to examine how technological functionality and external motivation interact in influencing user decisions. The main focus of this research is to investigate the role of Social Influence as a transactional accelerator that bridges the emotional drive resulting from the Fear of Missing Out phenomenon and live shopping algorithms with financial execution through the Paylater feature. By taking a case study in the urban area of DKI Jakarta, which has high digital penetration, this research is anticipated to address the existing gap in the literature concerning of consumer behavior on social commerce platforms.